La diva Virginia Fábregas: intersecciones entre su teatro y su vida, 1888-1950 - García Peña, Ana Lidia (Latin American Theatre Review, 2018)
This study presents the life story of Virginia Fábregas, a major diva of Mexico at the start of the twentieth century. The discussion focuses on the following issues: changes in the theatre between the late nineteenth and early twentieth centuries; the artistic life of Fábregas; her theatre; her image of elegance; and her complex and scandalous divorce. Theories of Pierre Bourdieu on distinction and of Guy Debord on spectacle are used to explain how the theater became a fundamental space of sociability for the Mexican bourgeoisie of the time and how the apotheosis of this process was precisely the Teatro Virginia Fábregas in terms of distinction,taste, and bourgeois classing. The essay builds on historical theatre sources that help reconstruct the various stages of Fábregas’s life.